2023
DOI: 10.26508/lsa.202201619
|View full text |Cite
|
Sign up to set email alerts
|

H4K20me1 plays a dual role in transcriptional regulation of regeneration and axis patterning inHydra

Abstract: The evolution of the first body axis in the animal kingdom and its extensive ability to regenerate makesHydra, a Cnidarian, an excellent model system for understanding the underlying epigenetic mechanisms. We identify that monomethyltransferase SETD8 is critical for regeneration inHydrabecause of its conserved interaction with β-catenin to fine-tune the associated gene regulatory network. Inhibition of SETD8 activity abolishes head and foot regeneration inHydra. Furthermore, we show that H4K20me1, the histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Recent evidence suggests that H4K20me1 is associated with increased chromatin accessibility at gene bodies, but is also readily converted to repressive trimethylated H4K20 (Shoaib et al, 2021). Gungi et al showed that H4K20 monomethylation via SETD8 is involved in both locus-specific repression and transcriptional activation during regeneration and axis patterning in the cnidarian Hydra (Gungi et al, 2023). Together with our findings, this suggests that H4K20 methylation may be a shared feature of chromatin regulation among cnidarian stem cells, to achieve specific gene activation.…”
Section: Twenty-two Predicted H4k20 Methyltransferase Also Activate E...supporting
confidence: 85%
“…Recent evidence suggests that H4K20me1 is associated with increased chromatin accessibility at gene bodies, but is also readily converted to repressive trimethylated H4K20 (Shoaib et al, 2021). Gungi et al showed that H4K20 monomethylation via SETD8 is involved in both locus-specific repression and transcriptional activation during regeneration and axis patterning in the cnidarian Hydra (Gungi et al, 2023). Together with our findings, this suggests that H4K20 methylation may be a shared feature of chromatin regulation among cnidarian stem cells, to achieve specific gene activation.…”
Section: Twenty-two Predicted H4k20 Methyltransferase Also Activate E...supporting
confidence: 85%
“…Recent evidence suggests that H4K20me1 is associated with increased chromatin accessibility at gene bodies, but is also readily converted to repressive trimethylated H4K20 [ 72 ]. Gungi et al showed that H4K20 monomethylation via SETD8 is involved in both locus-specific repression and transcriptional activation during regeneration and axis patterning in Hydra [ 73 ]. Together with our findings, this suggests that H4K20 methylation may be a common feature of chromatin regulation among hydrozoan stem cells to achieve specific gene activation, which may also be selectively conserved in other animals such as sea urchin.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the co-expression of a large number of predicted H4K20 methyltransferases at genome activation ( Fig 3 ) could be correlated with this chromatin remodeling activity, and the concomitant clearance of a maternal H4K20 methyltransferase variant ( Fig 3A ) suggests a maternal-to-zygotic chromatin regulatory transition for this mark. H4K20 methylation has been implicated in differential chromatin accessibility [ 72 , 73 ], and thus may participate in ensuring the activation of only specific transcriptional programs in embryonic cells. The potential for a similar expansion of H4K20 methyltransferase genes in sea urchin embryos ( S4 Fig ) raises the possibility that this represents an ancient mode of chromatin regulation that was only selectively maintained in certain animals, for reasons that remain to be discovered ( Fig 7B ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than disrupting PARP-1 function, we propose that this reduction in H4K20me1 may signify a regulatory shift in chromatin structure, priming these genes for transcriptional activation during heat shock, with PARP-1 playing an independent facilitating role. Moreover, existing studies have highlighted the dual role of H4K20me1, acting as a promoter of transcription elongation in certain contexts and as a repressor in others ( Barski et al, 2007 ; Nikolaou et al, 2017 ; Tanaka et al, 2017 ; Veloso et al, 2014 ; Fuchs et al, 2014 ; Abbas et al, 2010 ; Kapoor-Vazirani and Vertino, 2014 ; Shoaib et al, 2021 ; Gungi et al, 2023 ). The elevated enrichment of H4K20me1 in group B genes under normal conditions may indicate a repressive state that requires alleviation for transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%